Fast synthesis of fluorescent SiO2@CdTe nanoparticles with reusability in detection of H2O21. Issue 30 (14th August 2015) - Ge, Jiejie; Ren, Xiangling; Qiu, Xiaozhong; Shi, Haitang; Meng, Xianwei; Tang, Fangqiong
<x xml:space="preserve">Abstract</x> Fluorescent core/shell SiO2@CdTe NPs with different colours were synthesized conveniently and efficiently and applied to detection of H2O2 with reusability.